2022
DOI: 10.3390/atmos13050640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Levels of COVID-19 Pandemic Prevention and Control Measures on Air Quality: A Case Study of Jiangsu Province, China

Abstract: In order to control the spread of the COVID-19 pandemic, the prevention and control measures of public health emergencies were initiated in all provinces of China in early 2020, which had a certain impact on air quality. In this study, taking Jiangsu Province in China as an example, the air pollution levels in different regions under different levels of pandemic prevention and control (PPC) measures are evaluated. The implementation of the prevention and control policies of COVID-19 pandemic directly affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
3
2
0
Order By: Relevance
“…During the lockdown period, people's mobility and road transportation were restricted resulting into a massive drop in transport sector NO 2 emissions, which might have -6.87 -1.50 caused a higher drop in NO 2 concentration over the heavily urbanized areas, such as Kathmandu, compared to rural areas in the country. It suggests that the NO 2 would be more sensitive among the pollutants to the lockdown in urban areas, as a prior study conducted in Jiangsu Province, China, suggested (Ai et al, 2022). This result also agrees with a prior investigation conducted in the UK, which concluded that NO 2 reduction during lockdown was higher at urban traffic sites and lower at background sites (Jephcote et al, 2021).…”
Section: Change In No 2 Column Number Densitysupporting
confidence: 89%
See 3 more Smart Citations
“…During the lockdown period, people's mobility and road transportation were restricted resulting into a massive drop in transport sector NO 2 emissions, which might have -6.87 -1.50 caused a higher drop in NO 2 concentration over the heavily urbanized areas, such as Kathmandu, compared to rural areas in the country. It suggests that the NO 2 would be more sensitive among the pollutants to the lockdown in urban areas, as a prior study conducted in Jiangsu Province, China, suggested (Ai et al, 2022). This result also agrees with a prior investigation conducted in the UK, which concluded that NO 2 reduction during lockdown was higher at urban traffic sites and lower at background sites (Jephcote et al, 2021).…”
Section: Change In No 2 Column Number Densitysupporting
confidence: 89%
“…A study showed a 4.1% to 10.0% decrease in average NO 2 over Bangladesh, Pakistan, and India, while a 12.6% increase over the south Asia region during the lockdown period compared to the long-term averages (Upadhyay et al, 2022). The decrease in NO 2 column number density over Nepal obtained in the present study was comparable to that over India reported by Upadhyay et al Moreover, a study conducted in Jiangsu Province, China, showed a 12.0% decrease in NO 2 during the implementation of the most restrictive control measure to contain the COVID-19 pandemic (Ai et al, 2022), which was comparable to the findings of the present study. However, a 12.6% increase in the region-average NO 2 column number density during the lockdown has been reported over south Asia (Upadhyay et al, 2022), which suggested that the regional analysis may not represent the sub-regional scenario of Nepal.…”
Section: Change In No 2 Column Number Densitysupporting
confidence: 81%
See 2 more Smart Citations
“…Compared with 2019, the national average PM 2.5 , PM 10 , SO 2 , NO 2 , and CO concentrations decreased significantly during the period from 24 January to 30 April 2020, and the O 3 concentration did not change significantly or showed an upward trend in some areas [3][4][5]. With the resumption of work and production at the end of February, PM 2.5 and NO 2 concentrations in most cities began to increase gradually [6,7]. Compared with the previous Spring Festival holiday and the days before the Spring Festival, the anthropogenic emissions of PM 2.5 , SO 2 , and NO 2 during the Spring Festival in 2020 were significantly reduced, and the concentration of pollutants in most cities was significantly reduced [8,9].…”
Section: Introductionmentioning
confidence: 95%